If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 58 = -2(m + 4) * m Reorder the terms: 58 = -2(4 + m) * m Reorder the terms for easier multiplication: 58 = -2m(4 + m) 58 = (4 * -2m + m * -2m) 58 = (-8m + -2m2) Solving 58 = -8m + -2m2 Solving for variable 'm'. Reorder the terms: 58 + 8m + 2m2 = -8m + 8m + -2m2 + 2m2 Combine like terms: -8m + 8m = 0 58 + 8m + 2m2 = 0 + -2m2 + 2m2 58 + 8m + 2m2 = -2m2 + 2m2 Combine like terms: -2m2 + 2m2 = 0 58 + 8m + 2m2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(29 + 4m + m2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(29 + 4m + m2)' equal to zero and attempt to solve: Simplifying 29 + 4m + m2 = 0 Solving 29 + 4m + m2 = 0 Begin completing the square. Move the constant term to the right: Add '-29' to each side of the equation. 29 + 4m + -29 + m2 = 0 + -29 Reorder the terms: 29 + -29 + 4m + m2 = 0 + -29 Combine like terms: 29 + -29 = 0 0 + 4m + m2 = 0 + -29 4m + m2 = 0 + -29 Combine like terms: 0 + -29 = -29 4m + m2 = -29 The m term is 4m. Take half its coefficient (2). Square it (4) and add it to both sides. Add '4' to each side of the equation. 4m + 4 + m2 = -29 + 4 Reorder the terms: 4 + 4m + m2 = -29 + 4 Combine like terms: -29 + 4 = -25 4 + 4m + m2 = -25 Factor a perfect square on the left side: (m + 2)(m + 2) = -25 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| r^2-19t+18=0 | | r^2-9t+18=0 | | 1000=x(30-2x)(20-2x) | | -30a=-20 | | -30=-20 | | 7x-14=11x | | -2x-4=24 | | -2(2x-6)=20 | | -2(x+5)=30 | | 2(2x-6)=40 | | 4x-2x+2=16 | | x-5x+4=-8 | | 2x+8x=17 | | -7x+5x+2=20 | | x-8-3=10 | | 8z=40 | | 24x-3=15+45x | | 9t=-16t^2+60t | | -13y-7y=-140 | | 2x-7=20+12x | | 13y-7y=-140 | | -10x-3x=-39 | | 3x+4y+z= | | -4x-8x=48 | | 60*0-30x=-180 | | c=a+ab | | 3a(n+7)=43 | | 60y-30x=-180 | | 3p^2+12p+11=0 | | 3(2x-3)=63 | | c=(a*b)+a | | 15x-15=3x-129 |